Endohyphal bacterial communities modulate fungal responses to hyphosphere-associated bacteria in Fusarium - Simone Lupini; Lúrima Uane Soares Faria; Claudio Augusto Oller do Nascimento; Debora F. Rodrigues (Fungal Ecology, 2025)

High prevalence and genetic heterogeneity of adenoviruses at a psittacine breeding facility - Gabriele Lizzi; Simone Fasana; Guido Grilli; Giulia Quaglia; Sara Pedrazzoli; Giulia Graziosi; Elena Catelli; Laura Musa; Maria Cristina Rapi; Caterina Lupini (Veterinary Research Communications, 2024)
A polymerase chain reaction (PCR) survey was performed at an amateur parrot breeding facility in Italy to investigate the presence and molecular characteristics of adenoviruses. Eighty psittacine birds, belonging to seven parrot species, were sampled by cloacal swabs; in addition, 15 livers were collected from specimens that were found dead. Seventy-two out of 95 samples collected were positive for adenoviruses, with a prevalence rate of 75.8%. All seven psittacine species tested positive for at least one genus of the family Adenoviridae ; notably, adenoviral infection was found for the first time in the hooded parrot ( Psephotellus dissimilis ). Based on the sequences and phylogenetic analysis, 57 sequences were psittacine adenovirus 2, seven sequences were duck adenovirus 1 and two sequences were identified as psittacine adenovirus 5. The six remaining sequences showed low nucleotide and amino acid identity with the reference strains of accepted species or types, revealing the presence of novel adenoviruses belonging to the genera Aviadenovirus , Barthadenovirus and Siadenovirus . There were identical adenovirus sequences in both apparently healthy and dead birds suggesting that further investigation into the role and impact of these viruses on the health of psittacine birds is warranted.

Diversity of fungal microbiome obtained from plant rhizoplanes - Simone Lupini; Hang N. Nguyen; Demosthenes Morales; Geoffrey L. House; Sachin Paudel; Patrick S.G. Chain; Debora F. Rodrigues (Science of The Total Environment, 2023)